2008
DOI: 10.1097/scs.0b013e31816aaad4
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Dissection of the Arterial Supply of the Lips

Abstract: Previous investigators have not described some of the new anatomic variations or provided quantitative and analytical data of the arterial anatomy of the lips in as much depth as in this study. Dissections of 14 different facial sides of cadavers were done. Through investigating the arterial supply of the upper and lower lips, measurements were performed and statistically analyzed. The main arterial supply of the upper lip was from the superior labial artery (SLA, mean external diameter, 1.8 mm [SD, 0.74 mm]);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 18 publications
2
17
0
2
Order By: Relevance
“…Men have a facial muscle mass significantly larger and thicker, characterized by a higher functional activity that anticipates the appearance of wrinkles and makes them deeper. The lower third of the male face, on the other hand, shows fewer signs of aging than its female counterpart, due to the presence of more pilosebaceous annexes, and a more developed vascularization of the same area …”
Section: Resultsmentioning
confidence: 99%
“…Men have a facial muscle mass significantly larger and thicker, characterized by a higher functional activity that anticipates the appearance of wrinkles and makes them deeper. The lower third of the male face, on the other hand, shows fewer signs of aging than its female counterpart, due to the presence of more pilosebaceous annexes, and a more developed vascularization of the same area …”
Section: Resultsmentioning
confidence: 99%
“…It is observed bilaterally in 36–90% of cases after cadaveric dissection, but only in 17% of cases by CT angiography (Edizer et al, ; Pinar et al, ). As the external diameter of the ILA is <1 mm, resolution by CT angiography could be insufficient to detect every ILA branch (Park et al, ; Crouzet et al, ; Kawai et al, ; Pinar et al, ; Al‐Hoqail and Meguid, ).…”
Section: Resultsmentioning
confidence: 99%
“…In the second, it branches below the cheilion and ascends along the labiomental crease; this branch is sometimes defined as the horizontal labiomental artery (hLMA) to distinguish it from the ILA. Several vertical branches of the hLMA anastomose with the ILA routing along the first pattern or submental artery (SMA) (Kawai et al ; Al‐Hoqail and Meguid, ), which are defined as the vertical labiomental arteries (vLMA). In addition, an artery deeply proceeding along the labiomental crease toward the muscles or the periosteum of the mentum is known as the horizontal mental branch, sublabial artery, or cortical branch (Park et al ; Edizer et al, ; Loukas et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1314] In Table 2, diameters of inferior labial artery at origin are shown. [7101517] Earlier only one study has shown an internal diameter diameter of inferior labial artery measured; 0.8 mm (0.2-1.4 mm) in origin. [7] This study showed that inferior labial artery was located in the submucous layer in 77.27% cases and in 13.64% of the specimens this artery was in the superficial muscle layer of the orbicularis oris.…”
Section: Discussionmentioning
confidence: 99%